Deep breast pain during lactation: a case-control study in Sweden investigating the role of Candida albicans - Kirsti Kaski; Linda J. Kvist (BMC, 2018)
Abstract Background Deep breast pain during lactation, with or without accompanying nipple pain and soreness continues to be anecdotally linked to infection by Candia albicans despite lack of robust evidence in the literature that Candida albicans is the cause of women's breast symptoms. Methods A case-control study of breastfeeding women in Sweden with (n 35) and without (n 35) symptoms that may be attributable to Candida albicans was carried out. The symptoms were radiating, burning and penetrating or non-penetrating breast pain with or without associated nipple pain during or after breastfeeding. The primary aim of the study was to test the hypothesis that breastfeeding women with symptoms commonly associated with Candida albicans infection will have a growth of Candida albicans in their breast milk significantly more often than women without these symptoms. A secondary aim was comparison of breastfeeding self-efficacy, measured by the BSES-SF (Breastfeeding Self Efficacy Scale -Short Form), between cases and controls. Results None of the women in the control group and eight of the women in the case group showed a growth of Candida albicans in their breast milk (p <  0.01), which confirms the hypothesis. There were no statistically significant differences in severity or type of symptoms between those in the case group with and without growth of Candida albicans in their breast milk. Results of the BSES-SF measurement showed no statistically significant differences between cases and controls. However, when analyses were stratified for parity, multiparous controls showed statistically significant higher scores for breastfeeding self-efficacy than multiparous cases. Conclusions Neither clinical symptoms nor microbial cultivation appear to be reliable means for making a diagnosis of Candida albicans infection of the breast. Skilled breastfeeding consultants should offer support and help with positioning, attachment and identification of physical impediments to successful breastfeeding. Professionals should be aware that it is possible that uncertainty in the breastfeeding situation may to some extent account for mothers' breast symptoms. The ISRCTN (International Standard Randomised Controlled Trial Number) identity for this case-control study is ISRCTN88839993. The study was retrospectively registered on 30 November 2016.